Aspek Sosial Budaya Sebagai Penunjang Kebijakan Pendidikan Di Kabupaten Kepulauan Yapen Provinsi Papua: Analisis Wacana Keberpihakan Otsus Papua - KLARA, ANTONIA (Melanesia : Jurnal Ilmiah Kajian Bahasa dan Sastra, 2017)
This article aims to reveal the discourse on government to establish policies through the use of financial leverage a variety of revenue source to find program activities in order to build a quality education for the people in the District Yapen Island Province of Papua. The fact today that increasing per capita income, the ability of people to pay for education becomes higher, so demand will be higher level of education and time for school to be longer. In the perspective of economics discourse, in essence that economic development to all regions in Indonesian has prompted the central government to carry out political and economic control of the local government.In principle, this paper elaborated in the framework of development- oriented local government has very large fiscal dependency on transfers from the center to the regions at both provincial and district/city. For the special autonomy funds received by the provincial government/ district became part of the transfer is very important and eagerly anticipated in supporting the development of various areas in the District Yapen Island Province of Papua.